The behavioural consequences of perceived service quality: A study of the Indian telecommunication industry - Deepika Jhamb; Amit Mittal; Pankaj Sharma (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The telecom industry in India has witnessed substantial growth over the last decade. Rapid growth of telecommunications is opening up the doors for many telecom players from Europe, Asia and other parts of the world, resulting in increased competition and tariff reductions. In the present competitive environment, the services perceived by the customers and their behavioural intentions play a pivotal role in the customer switching process among service providers. With the changing expectations of service quality, it becomes imperative to discover the gap between customer expectations and customer perception. In this context, the aim of the present study is to identify the existing gap between customer expectations and perceptions and investigate the relationship between post-experience perception of service quality and customers' behavioural intentions. The data was collected from 500 customers in Delhi NCR, India. Paired sample t-test and multiple correlation analysis were performed. The results of the study points out the key areas wherein the service gaps are considerably high such as reliability and responsiveness. The customer behavioural intentions, such as 'Complain to customer service if a problem occurs', 'Switch to another service provider' and 'Reducing the usage with a particular service provider', have shown a strong relationship with quality of service. The findings of the study confirm that the perceptions of customers regarding the quality of service received definitely have an impact on their behaviour.
Keywords: L80; L96; D10; 650; service quality; expectations; perceptions; behavioural intentions; telecom service providers